Analysis of the effects of city economic growth in South Sulawesi - Fadilah Fadilah; Indraswati T.A. Reviane; Retno Fitrianti (Institute of Computer Science (IOCS), 2023)
Determining the center of growth in a region has a very important role in determining the direction of policies and regulations for the central and regional governments in carrying out regional development. Determination of growth centers has a function for equitable distribution of development in all regions, facilitating coordination between regions and maximizing the management of existing potential and natural resources. This study aims to determine the effect of government spending, investment and city economic growth to the surrounding districts through the city's economic growth. This study used Path Analysis with the software used, AMOS, to perform data processing and analysis. The results of this study indicate that there is no effect of government spending in three cities, namely the cities of Makassar, Parepare and Palopo to the surrounding districts indirectly through the city's economic growth and there is investment effect from the city of Makassar to the surrounding districts indirectly through the economic growth of the city of Makassar.